Claiming civic virtue gendered network memory in the Mara Region, Tanzania - Shetler, Jan Bender 1954- (Women in Africa and the diaspora, 2019)
Among communities in the Mara region of Tanzania, it is considered men2019s responsibility to maintain 201Chistory.201D But when Jan Bender Shetler2019s questions turned to specific familial connections within the village, she discovered her male informants had to occasionally leave the room2015to ask their wives for clarification. The result is an original and wide-ranging investigation of the gendered nature of historical memory and its influence on the development of the region over the past 150 years. Shetler2019s exploration of these oral traditions and histories opens exciting new vistas for understanding how women and men in this culture tell their stories and assert their roles as public intellectuals2015with important implications for research in African and gender studies, and the history of ethnicity and nationalism